2006
DOI: 10.1007/s10903-006-9015-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors in the Delayed HIV Presentation of Immigrants in Northern California: Implications for Voluntary Counseling and Testing Programs

Abstract: To describe the determinants of delayed HIV presentation in one Northern California County, the authors identify persons with an opportunistic infection (OI) at HIV diagnosis. From 2000-2002, a sample of HIV patients attending a public AIDS program (n=391) were identified. Immigrants composed 24% of our sample; 78.7% of immigrants were Hispanic. Immigrants, compared to U.S.-born patients, presented with lower initial CD4+ counts at diagnosis than U.S.-born patients (287 cells/mm(3) vs. 333 cells/mm(3), p=0.143… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 19 publications
7
74
0
1
Order By: Relevance
“…Consistent with prior research, factors identified as barriers to HIV testing included misperceptions about HIV, lack of knowledge on the importance of knowing one's HIV status, lack of access to testing, and fears of deportation [24][25][26][27]. These factors have been found in other studies among vulnerable groups as barriers to HIV testing [6,[28][29][30].…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with prior research, factors identified as barriers to HIV testing included misperceptions about HIV, lack of knowledge on the importance of knowing one's HIV status, lack of access to testing, and fears of deportation [24][25][26][27]. These factors have been found in other studies among vulnerable groups as barriers to HIV testing [6,[28][29][30].…”
Section: Discussionsupporting
confidence: 76%
“…Se conocen diferentes factores que favorecen la ausencia o el retraso de contacto de los inmigrantes con los servicios de salud: barreras lingüísticas, nivel sociocultural, situación administrativa, estigma social, desconocimientos de aspectos relacionados con la infección [28][29] . Hemos encontrado un mayor riesgo de PEA en todas las áreas estudiadas (excluyendo América del Norte, Asia y Oceanía debido al escaso número nuevos diagnósticos) en relación con Europa Occidental.…”
Section: Vihunclassified
“…Moreover, Mexican-born Latinos are more likely than U.S.-born Latinos to present a short HIV-to-AIDS interval, implying delayed testing and inadequate care and treatment (Espinoza, Hall, Selik, & Xiaohong, 2008;Tang, Levy, & Hernandez, 2008). In addition, in two California studies, it was more likely that Latino immigrants were infected with HIV in the U.S. than in their home countries (Harawa et al, 2002;Levy et al, 2007).…”
mentioning
confidence: 99%